Nonlinear modeling of the arm dynamics for the manipulators with reverse sensory validation. (13th December 2019) - Bozek, Pavol
The article deals with design issues of a system for regulating and controlling of the pendulum amplitude using an inertial system and a stepper motor. Basis of the solution is the pendulum theory and its mathematical model, respectively mathematical modeling of the pendulum trajectory. The aim is to derive the mathematical equation of the pendulum, calculate its oscillation period, and plot the oscillation of the pendulum model with damping or actuating in real time on a case study, as proposed by the authors. Following is the description of the inertial system, which is represented by an accelerometer and an angle sensor. Information about the velocity, acceleration, and position of the pendulum are acquired by mathematical derivations. The proposed hardware model and amplitude control algorithm for the microcontroller together with a brief description of the concluded experiments, which were focused on the accuracy of measurement and evaluation of all acquired data, is described next. The obtained results can be applied in the field of robotics, mainly due to its accuracy of trajectory calculation and plotting but also by reverse validation control of the movement of the monitored robot effectors.